Determinants of Long-Term Contraceptive Method Use in Madiun, East Java: Application of Social Cognitive Theory - Kartika -; Uki Retno Budihastuti; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Indonesia ranks 5 in the world by the number of population. It has Total Fertility Rate of 2.6, which is higher than average rate in South East Asia. In order to control population growth the Indonesian Government has attempted to increase the utilization of the long-term contraceptive method. This study aimed to determine determinants of long-term contraceptive method use in Madiun, East Java with the application of social cognitive theory.Subjects and Method: This was an analytic observational study with case control design. Study subjects consisted of 50 women of reproductive age who had used long term contraceptive method and 100 similar women who had not. The dependent variable was use of long-term contraceptive method. The independent variables were education level, knowledge, attitude, culture, information access, and decision maker. The data were collected using a set of questionnaire and analyzed by path analysis in STATA.Results: Use of long-term contraceptive method were positively affected by high education level (b= 1.31; 95% CI= 0.13 to 2.50; p=0.029), positive attitude (b= 2.45; 95% CI= 1.47 to 3.43); p<0.001), and joint decision making (b= 2.02; 95% CI= 0.91 to 3.13; p<0.001). Joint decision making was affected by positive attitude (b= 1.27; 95% CI= 0.58 to 1.96; p<0.001). Positive attitude was affected by good knowledge (b=0.75; 95% CI= 0.09 to 1.49; p=0.047) and positive culture (b= 1.44; 95% CI= 0.70 to 2.17; p<0.001). Good knowledge was affected by good information access (b= 0.96; 95% CI= 0.20 to 1.63; p= 0.005).Conclusion: Use of long-term contraceptive method is positively affected by high education level, positive attitude, and decision making.Keywords: Use of long term contraceptive method, women of childbearing age, family planningCorrespondence: Kartika. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: tsurayya.kartika@gmail.com. Mobile: +6281803339900.Journal of Health Promotion and Behavior (2017), 2(4): 313-322https://doi.org/10.26911/thejhpb.2016.02.04.03